Fortuna y fatum: la contingencia en el desarrollo de la historia según Amiano Marcelino - Santos Yanguas, Narciso (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
For Ammianus one should always take into account an indeterminate element of chance in historical development. It would explain in itself historical reality. This way, chance would appear associated to a higher power, Fortune as divine guide, in itself an arbiter of human actions. Finally, fatum as fate usually appears as hostile to human enterprises, its positive influx being very limited.